Rapeseed (Brassica napus): Processing, Utilization, and Genetic Improvement - Nadia Raboanatahiry; Huaixin Li; Longjiang Yu; Maoteng Li (Agronomy, 2021)
Brassica napus L. is a vegetable oil crop, commonly known as rapeseed (or canola). It is widely used as a source of oil and protein for food and industrial applications, but also as a remedy, and in a field of attraction or as an ornament due to its diverse flower colors. Every part of rapeseed is useful, even the waste, which could be used to feed animals, or recycled. In this review, the use of rapeseed in these applications is presented, starting with the preparation of oil and protein from the seeds, before their release in the market, to the utilization of natural unprocessed rapeseed. Progress in rapeseed exploitation for food, remedy, energy source, and industrial applications are analyzed to show variability in diverse findings, to provide insights and progressive descriptions of rapeseed usage to other scholars. Moreover, advancements in breeding for rapeseed improvement were described. In the future, strategies could be developed or improved to avoid or decrease crop losses, but also to increase interest in propagating the valuable traits of rapeseed.